FRAMING POLITICAL DYNASTIES IN KOREAN ONLINE NEWS OF INDONESIA’S ELECTION - Ayuningsih, Adinda Safitri; Triarisanti, Risa; Lubis, Arif Husein (Universitas Islam Sumatera Utara (UISU), 2025)
Language choices are often used to reveal and reflect writers’ perspectives on certain issues, particularly constructed in online news media. Such language choices can affect readers’ stance in evaluating the issues being raised, leading to framing the news. This study aims to reveal the framing of Indonesia’s political dynasty during Indonesia’s regional election in 2024 in online Korean News. This study applied Pan and Kosicki’s framing analysis method to uncover the news construction in three Korean news: Seoul Economic Daily, Kyunghyang Shinmun, and Yonhap News, through syntactical, script, thematic, and rhetorical structures. The analysis results show that the syntactical structures on three news highlights 대규모 시위 (large-scale demonstration) as the main cause of the cancellation of the candidacy. Meanwhile, the script structures are structurally complete, holding all the 5W+1H elements. On the thematic structure, the three Korean news reports surrounded the same issue, the change of regional election law, also using the same pronouns: 장남 (first son) and 차남 (second son) to refer to the main figure being discussed. Lastly, the three news articles have distinctive styles in their rhetorical structures while delivering the information, but still attempt to shape audiences’ opinions through diction, character quotations, and narratives about the integrity or ambition of power. Based on these findings, this study recommends further research by applying a critical discourse analysis approach to unpack the interplay between language use and power relations, concerning with critical issues discussed in online news.